Entrepreneurial Ecology-Based Indigenous People Learning Model in Utilizing the Ammatoa Kajang Customary Area - Irwanto Gani; Achmad Hufad; Oong Komar; Jajat S Ardiwinata (Postgraduate, University of Mataram, 2023)
This journal article focuses on the development of an ecological entrepreneurship-based learning model for the indigenous community of Ammatoa Kajang, who reside in South Sulawesi, Indonesia. The community possesses rich ecological knowledge and cultural heritage intertwined with their environment. However, external pressures and modernization threaten their cultural and ecological sustainability. This research aims to create a learning model that integrates ecological entrepreneurship with Ammatoa Kajang traditions using ethnographic methods. The article discusses challenges faced by the indigenous community in preserving their cultural values while adapting to modern economic changes. The Ammatoa Kajang region, abundant in natural resources and cultural significance, confronts issues such as climate change and rapid development. Ecological entrepreneurship emerges as a solution, aligning economic efforts with environmental preservation and cultural heritage. This approach promotes environmentally conscious business practices and addresses ecological challenges. Ethnographic methodology is crucial for understanding the intricate relationship between the community, ecology, and the economy. Through ethnographic research, this study explores the cultural and ecological context of Ammatoa Kajang, offering insights into their traditional ecological knowledge and practices. This study presents a comprehensive approach to driving sustainable economic development while respecting cultural values and preserving the environment.